Proportion and factors of death among preterm neonates admitted in University of Gondar comprehensive specialized hospital neonatal intensive care unit, Northwest Ethiopia - Yismaw, Ayenew Engida (BMC Res Notes, 2018)
OBJECTIVE: Neonatal mortality accounts for 43% of under-five child mortality in Ethiopia where preterm is the second leading cause of neonatal death and steadily increased in low-income countries. Therefore, assessing the proportion of death and associated factors among preterm neonates has a paramount importance in designing an effective strategy to intervene and achieve sustainable development goal. RESULTS: In this study proportion of preterm neonatal death in this study was 28.8% [95% CI (25.1, 32.9)]. Complications during index pregnancy [AOR = 1.92, 95% CI (1.09, 3.38)], gestational age [AOR = 0.78, 95% CI (0.69, 0.91)], small for gestational age [AOR = 2.42, 95% CI (1.33, 4.38)], APGAR score at birth < 7 [AOR = 2.39, 95% CI (1.34, 4.27)], hyaline membrane disease [AOR = 5.15, 95% CI (2.83, 9.36)], neonatal respiratory distress at admission [AOR = 1.93, 95% CI (1.13, 3.31)], presence of jaundice [AOR = (3.39, 95% CI (1.90, 6.05)], received kangaroo mother care [AOR = 0.13, 95% CI (0.05, 0.35)], and hypoglycemia at admission [AOR = 3.86, 95% CI (2.12, 7.06)] were statistically significant. The proportion of preterm neonatal death was high. Ministry of health and responsible organizations should give special attention for preterm neonates to prevent life-threatening complications.